Benchmarking analogue models of brittle thrust wedges. (November 2016) - Schreurs, Guido; Buiter, Susanne J.H.; Boutelier, Jennifer; Burberry, Caroline; Callot, Jean-Paul; Cavozzi, Cristian; Cerca, Mariano; Chen, Jian-Hong; Cristallini, Ernesto; Cruden, Alexander R.; Cruz, Leonardo; Daniel, Jean-Marc; et al.
Abstract: We performed a quantitative comparison of brittle thrust wedge experiments to evaluate the variability among analogue models and to appraise the reproducibility and limits of model interpretation. Fifteen analogue modeling laboratories participated in this benchmark initiative. Each laboratory received a shipment of the same type of quartz and corundum sand and all laboratories adhered to a stringent model building protocol and used the same type of foil to cover base and sidewalls of the sandbox. Sieve structure, sifting height, filling rate, and details on off-scraping of excess sand followed prescribed procedures. Our analogue benchmark shows that even for simple plane-strain experiments with prescribed stringent model construction techniques, quantitative model results show variability, most notably for surface slope, thrust spacing and number of forward and backthrusts. One of the sources of the variability in model results is related to slight variations in how sand is deposited in the sandbox. Small changes in sifting height, sifting rate, and scraping will result in slightly heterogeneous material bulk densities, which will affect the mechanical properties of the sand, and will result in lateral and vertical differences in peak and boundary friction angles, as well as cohesion values once the model is constructed. Initial variations in basal friction are inferred to play the most important role in causing model variability. Our comparison shows that the human factor plays a decisive role, and even when one modeler repeats the same experiment, quantitative model results still show variability. Our observations highlight the limits of up-scaling quantitative analogue model results to nature or for making comparisons with numerical models. The frictional behavior of sand is highly sensitive to small variations in material state or experimental set-up, and hence, it will remain difficult to scale quantitative results such as number of thrusts, thrust spacing, and pop-up width from model to nature. Highlights: A quantitative comparison of thrust wedge models from 15 analogue modeling laboratories is presented. Analogue models show variability, most notably for surface slope, thrust spacing and number of forward and backthrusts. Model variability is most likely controlled by initial variations in basal friction. Our comparison highlight the limits of up-scaling quantitative analogue model results to nature.